Compositionally Designed 2D Ruddlesden–Popper Perovskites for Efficient and Stable Solar Cells. Issue 4 (1st February 2021) - Wei, Yi; Chen, Baoquan; Zhang, Fan; Tian, Yuyang; Yang, Xichuan; Cai, Bin; Zhao, Jijun
Abstract : Perovskite solar cells have emerged as one of the most promising candidates for next‐generation solar cells. However, their instability remains challenging for practical applications. Here, the authors aim to enhance the stability and efficiency simultaneously by tuning the organic components in 2D Ruddlesden−Popper perovskites (2D‐RPPs). Four groups of 2D‐RPPs are prepared and the influence of 4‐fluorophenethylammonium (FPEA) and formamidinium (FA) cations on the film properties and device performance are investigated. The (FPEA)2 (FA)8 Pb9 I28 film is found to be exceptionally vertically orientated, showing enhanced charge transport and lower defect density. Its absorption edge substantially extends in the IR region, which greatly increases the photocurrent. A high efficiency of 16.15% along with a V oc of 1.07 V and a J sc of 20.88 mA cm −2 is achieved for the (FPEA)2 (FA)8 Pb9 I28 solar cell. Notably, the (FPEA)2 (FA)8 Pb9 I28 film exhibits good humidity stability and remarkably enhanced thermal stability. Its unencapsulated device maintains 95% of its starting efficiency after 2112 h when exposed to ambient air with 30–70% relative humidity, which is superior than those of the reported (PEA)2 (MA)8 Pb9 I28 and (FPEA)2 (MA)8 Pb9 I28 solar cells. The study demonstrates that enhanced performance of 2D‐RPPs can be obtained by strategically designing organic compositions, which paves an avenue toward the commercialization of 2D‐RPP devices. Abstract : A group of new 2D‐RPPs is compositionally designed to achieve enhanced stability and efficiency of solar cell simultaneously. The (FPEA)2 (FA)8 Pb9 I28 film exhibits high crystallinity, low defect density and large carrier mobility. Its reduced bandgap greatly increases the photon utilization. Consequently, high‐performance solar cell with PCE of 16.15% is obtained. This device shows significantly improved thermal and humidity stability. (FPEA=4‐fluorophene‐thylammonium; FA=formamidinium).